Sosialisasi Penyusunan Best Practice pada Guru SDN 10 Mungguk Ibul Kecamatan Sukadana Kabupaten Kayong Utara - Jupitasari, Mellisa; Sulissusiawan, Ahadi; Wartiningsih, Agus; Sanulita, Henny; Syahrani, Agus; Khairullah, Khairullah (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Socialization of best Practices for the teachers of SDN 10 Mungguk Ibul, Sukadana, Kayong Utara Regency, is essential in preparing and equipping teachers with writing skills (best Practices). This is necessary for teachers to continuously improve the quality of teaching and enhance students' learning achievements optimally, enabling them to meet the demands of the times. Method used to enhance teachers' abilities and skills in creating best Practices is socialization. The results of this socialization activity are: (1) Teachers understand the meaning of best Practices, (2) teachers know how to implement best Practices in the field of education, (3) teachers understand the benefits of best Practices, (4) teachers understand how to apply best Practices, (5) teachers know examples of best Practice themes, (6) teachers understand the differences between Classroom Action Research and best Practices, and (7) teachers know how to write best Practices. Therefore, this socialization is important for teachers.